Working with experience : animating learning - Boud, David; Miller, Nod (Routledge, 1996)
"Much is known about teaching and being taught. Far less is known about how we learn, and, in particular, how we learn outside the classroom. Yet this is in fact where most learning takes place. One especially neglected area is the role that people other than the learner play in facilitating learning. This role is undertaken not only by teachers, trainers, parents and counsellors, but also by managers, supervisors, caregivers and friends." "This book brings together the experiences of a number of practitioners, who write from often strongly contrasting perspectives; these include feminism, critical pedagogy and post-modernism and different psychological perspectives - Gestalt, humanistic, clinical and transpersonal. The authors come from a wide range of backgrounds, including adult, higher and teacher education, community work, organisational development and psychotherapy." "Each chapter is grounded not only in professional practice and theory, but also in personal experience. The book provides fascinating insights into what some good practitioners do to promote learning, and how they make sense of this."--Jacket